Mortality in pediatric hydrocephalus. (15th July 2021) - Tully, Hannah M; Doherty, Dan; Wainwright, Mark
Abstract : Aim: To clarify the extent to which medical comorbidities and goals‐of‐care decisions influence death among individuals with childhood‐onset hydrocephalus. Method: This was a retrospective cohort study of 1705 individuals (759 males, 946 females, mean age 11y 5mo, SD 6y 6mo, range 0–37y 7mo at last follow‐up) with childhood‐onset hydrocephalus, of whom 88 (5.2%) were deceased. Existing medical records, death records, and publicly available internet sources were analyzed. We estimated hazard ratios for putative risk factors through Cox regression based upon 10 529 person‐years of data and quantitatively and qualitatively analyzed the circumstances surrounding each death. Results: Mortality did not differ statistically by demographic factors, although higher proportions of non‐White and Hispanic individuals were deceased. Most deaths were related to medical comorbidities rather than hydrocephalus itself. Of the 14 deaths directly related to hydrocephalus, seven were caused by shunt complications and four occurred after decisions to forgo treatment, apparently in response to poor outcomes predicted by the medical team. Half the deaths were preceded by shifts to comfort‐based care; however, these decisions appeared to substantially change the patient's clinical trajectory only half the time. Interpretation: Children are more likely to die with, rather than from, hydrocephalus. Our results emphasize the complexities of medical decision‐making and the influence of clinicians in guiding these choices.